PENERAPAN SISTEM INFORMASI PENJUALAN TOKO PADA UKM SEPATU CARDOLA SRAGEN - Atika Jauharia Hatta; Doddy Hapsoro; Y. Yohakim Marwanta; Efraim Ferdinan Giri; Shita Lusi Wardani; Deranika Ratna Kristiana (Universitas Majalengka, 2023)
Abstract The purpose of the Community Partnership Program for Small and Medium Enterprises is to develop and train a store sales information system to improve the ability of SME partners to manage their shoe store sales. So far, SME partners have never recorded how many shoes they have in stock, so if there is a reduction in inventory due to loss or theft, they cannot identify them. So far, SME partners have only done manual records regarding the number and types of shoes sold. The marketing of shoe sales is mostly done in stores, so the marketing reach is not too broad. The use of online-based marketing networks only uses Instagram, which may not have a not very broad space, and the available applications cannot record the number of shoes owned. Based on the problems mentioned above, the servant feels it is necessary to develop a store sales information system as an effort to record inventory accounting and a website to expand marketing reach. After the development of the information system is complete, it is necessary to have training on the use of the system. The results obtained from this training are increased knowledge and skills of SMEs in recording inventory and marketing their products, which is expected to increase business sales. Keywords: online marketing; community partnership program; Cardola shoes; small and medium enterprises